Progressive multi-component home-based physical therapy for deconditioned older adults following acute hospitalization: a pilot randomized controlled trial. (August 2016) - Stevens-Lapsley, Jennifer E; Loyd, Brian J; Falvey, Jason R; Figiel, Greg J; Kittelson, Andrew J; Cumbler, Ethan U; Mangione, Kathleen K
Objective: To determine whether a progressive multicomponent physical therapy intervention in the home setting can improve functional mobility for deconditioned older adults following acute hospitalization. Design: Randomized controlled trial. Setting: Patient homes in the Denver, CO, metropolitan area. Participants: A total of 22 homebound older adults age 65 and older (mean ± SD; 85.4 ±7.83); 12 were randomized to intervention group and 10 to the control group. Intervention: The progressive multicomponent intervention consisted of home-based progressive strength, mobility and activities of daily living training. The control group consisted of usual care rehabilitation. Measurements: A 4-meter walking speed, modified Physical Performance Test, Short Physical Performance Battery, 6-minute walk test. Results: At the 60-day time point, the progressive multicomponent intervention group had significantly greater improvements in walking speed (mean change: 0.36 m/s vs. 0.14 m/s, p  = 0.04), modified physical performance test (mean change: 6.18 vs. 0.98, p  = 0.02) and Short Physical Performance Battery scores (mean change: 2.94 vs. 0.38, p  = 0.02) compared with the usual care group. The progressive multicomponent intervention group also had a trend towards significant improvement in the 6-minute walk test at 60 days (mean change: 119.65 m vs. 19.28 m; p  = 0.07). No adverse events associated with intervention were recorded. Conclusions: The progressive multicomponent intervention improved patient functional mobility following acute hospitalization more than usual care. Results from this study support the safety and feasibility of conducting a larger randomized controlled trial of progressive multicomponent intervention in this population. A more definitive study would require 150 patients to verify these conclusions given the effect sizes observed.